Application of Geographic Information Systems to Monitor Dengue Fever Surveillance in Tha Kham Subdistrict, Panare District, Pattani Province - Sakphet, Norathep; Jitrugtham, Chatirot; Bunjan, Annop; Saknukul, Phatthira; Somjit, Pikul (KKU Science Journal, 2024)
The objectives of this research were to 1) survey and prepare a database, 2) develop geographic information technology system, and 3) evaluate the geographic information technology system to monitoring dengue surveillance in Tha Kham sub-district, Panare District, Pattani Province. There are 5 stages of research: (1) data collection, (2) system design, (3) system development, (4) system testing and (5) system evaluation by applying the System Development Life Cycle (SDLC) as a guideline for development. This research used a convenience sampling method with 40 public health officials, village health volunteers, and local residents. The results of the research showed that: 1) survey and storage of a spatial database of the addresses of dengue patients in Tha Kham sub-district, Panare District, Pattani Province, has determined the types of data, such as names, locations, and coordinates, by collecting data from 16 field trips. 2) Results of Geographic Information Technology Development showed that the system user can collect patient data and display current location. 3) The results of the evaluation of the effectiveness of geographic information technology to monitor dengue surveillance in Tha Kham Sub-district, Panare District, Pattani Province from 3 experts found that the data storage system was highly effective ( = 4.25, S.D. = 0.50), and the results of the satisfaction assessment of 40 users showed that the respondents had a high level of satisfaction ( = 4.24, S.D. = 0.50) in all topics.